Informationsüberlastung durch E-Mails - Ein Modell der Auslöser - Kammerer, Sebastian; Hetzenecker, Jochen; Sprenger, Sebastian; Amberg, Michael (Multikonferenz Wirtschaftsinformatik 2012, 2012)
In diesem Artikel wird, basierend auf den etablierten Modellen von Dabbish und Kraut sowie Franz, ein Modell zur Darstellung der Auslöser von Informationsüberlastung durch E-Mails abgeleitet. Die Ausgangsmodelle werden um zusätzliche Auslöser erweitert, welche im Rahmen einer Literaturanalyse hochrangiger IS Journals und IS Conferences identifiziert wurden. Das entwickelte Modell beinhaltet 14 divergierende Ursachen für die Informationsüberlastung durch E-Mails in den Kategorien „Merkmale der Informationen“, „Technische Merkmale“ und „Persönliche Merkmale“. Darüber hinaus beeinflussen die vier Moderatorvariablen „Alter“, „Geschlecht“, „E-Mail-Client“ und „Zugangsart“ die Wirkung der Auslöser auf die Informationsüberlastung durch E-Mails. Zur späteren Validierung des Modells wurden für die Variablen entsprechende Konstrukte identifiziert bzw. abgeleite

The Impact of Mental Representations on ICT-Related Overload in the Use of Mobile Phones - Saunders, Carol; Wiener, Martin; Klett, Sabrina; Sprenger, Sebastian (Journal of Management Information Systems, 2017)
AbstractThe use of information and communication technology (ICT) can be accompanied by the epiphenomenon of ICT-related overload, or the emotional and cognitive state that occurs when individuals are unable to efficiently retrieve and process information delivered by or associated with these technologies. While prior research tends to ascribe this phenomenon to the amount of information delivered, this study presents and provides significant empirical support for an expanded cognitive perspective of ICT-related overload, which views individuals’ information-processing capabilities as being reliant on differences in mental representations associated with cultural, demographic, and experiential factors. Specifically, based on a survey with 1,004 mobile phone users, we find that (1) polychronic individuals experience less ICT-related overload than monochronics; (2) memories of past emotional and cognitive overload increase ICT-related overload; and (3) age has inverse effects on different overload dimensions. Altogether, our findings challenge myths about information overload and multitasking, support a multidimensional conceptualization of ICT-related overload, and suggest ways that managers can reduce overload and leverage polychronicity.
Keywords: cognitive overload; communication overload; emotional overload; feature overload; ICT-related overload; information overload; mental representations; mobile phone use; polychronicity